Influence of ecologically friendly cores on surface quality of castings based on magnesium alloys - P. Lichý; J. Beňo; P. Lackova; M. Morys (Metalurgija, 2014)
Constructional materials as Al - alloys can be replaced by other materials with high strength to low mass density ratio, e.g. Mg-alloys. In order to pre-casting of holes and cavities cores based on pure inorganic salt can be applied due to easy cleaning of even geometrically complex pre-cast holes. This technology is applied mainly for gravity and low-pressure casting technology. This contribution is aimed at studying of mutual interaction of the Mg-alloy and the salt core. Experiments were focused on surface quality; macro- and microstructure of testing casting samples determination. Metallographic analysis and scanning electron microscope (SEM) with X-ray energy-dispersion superficial and spot microanalysis (EDAX) were employed.